The Application of Discrete Event Simulation (DES) to Enhance Wait Times and Space Utilization of a Multi-Department Clinic - Zamani, Zahra; Spence, Timothy J. (International Journal of Environment, Architecture, and Societies, 2023)
There has been an increasing demand for outpatient services that support patient experience and quality of care. Consequently, healthcare systems aspire to reduce operational costs and improve resource utilization through different strategies. Given the complexity of multi-department outpatient healthcare facility operations, DES has been recognized as an effective tool for evaluating performance outcomes and design decisions. The purpose of this study was to introduce Discrete Event Simulation (DES) as an effective tool in the architecture planning of a multi-department outpatient clinic. The DES integrated patient flow, schedules, proposed layout, and staffing information to identify space and staff utilization, wait for the provider (WFP), and wait for the room (WFR). The study explored the effects of pooling decentralized registration desks into a centralized desk and staffing with additional kiosks for the primary care departments. We also converted underutilized exam rooms into telehealth rooms, flexible consult-exam rooms, and dedicated pediatric waiting areas. registration pooling and kiosks improved staff resource utilization. Allocating additional providers and exam rooms to departments reduced their WFP and WFR. DES indicated minimal operational effects of transitioning underutilized exam rooms to alternate functions. This finding enabled us to determine if space allocation modifications negatively affected operations. The findings suggest the effectiveness of DES in analyzing the impact of alternative design strategies on operational outcomes through a data-driven approach. This understanding is valuable, as improved resource allocation and streamlined operation are associated with cost reduction and enhanced patient and staff satisfaction.